2014
DOI: 10.1017/s0007114514000075
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of probiotics on the duration of illness in healthy children and adults who develop common acute respiratory infectious conditions: a systematic review and meta-analysis

Abstract: Recent systematic reviews have reported a positive, although modest, effect of probiotics in terms of preventing common cold symptoms. In this systematic review, the effect of probiotics, specifically Lactobacillus and Bifidobacterium strains, on the duration of acute respiratory infections in otherwise healthy children and adults was evaluated. To identify relevant trials, eight databases, including MEDLINE, Embase, the Cochrane Database of Systematic Reviews (CDSR), the Cochrane Central Register of Controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
179
4
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(189 citation statements)
references
References 24 publications
0
179
4
6
Order By: Relevance
“…Strains of the Lactobacillus genus are widely acknowledged to be beneficial, and their properties have been reviewed extensively (20). Given their widespread association with a variety of different environments, including dairy, meat, vegetable, and grain-fermented foods and as commensals in the gastrointestinal tract, this genus has been widely consumed and also has been used in dietary supplements to promote general health and well-being (21)(22)(23). Recent human microbiome studies have identified Faecalibacterium prausnitzii as an organism with antiinflammatory properties and have reported it to be an indicator microbial population that was lowered in subjects with Crohn's disease and ulcerative colitis (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…Strains of the Lactobacillus genus are widely acknowledged to be beneficial, and their properties have been reviewed extensively (20). Given their widespread association with a variety of different environments, including dairy, meat, vegetable, and grain-fermented foods and as commensals in the gastrointestinal tract, this genus has been widely consumed and also has been used in dietary supplements to promote general health and well-being (21)(22)(23). Recent human microbiome studies have identified Faecalibacterium prausnitzii as an organism with antiinflammatory properties and have reported it to be an indicator microbial population that was lowered in subjects with Crohn's disease and ulcerative colitis (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…So the regulation of E. purpurea on Th1 and Th2 is totally different (Mosmann & Coffman, 1989). It has been reported that E. purpurea directly affected the immune system such as T lymphocyte, macrophage, dendritic cell (Cech et al, 2010;King et al, 2014). IL-2 was proven to promote the proliferation of T cells and enhance the cellular immunity, associated with the production of IgM and IgG (Cozzi et al, 1995).…”
Section: The Effect Of Ee On Immunoregulatory Cytokines and Immunoglomentioning
confidence: 99%
“…Fructooligosaccharides (FOS) have important beneficial physiological effects such as low cariogenicity, a prebiotic effect, improving mineral absorption, and decreasing the levels of serum cholesterol, triacylglycerols, and phospholipids. Currently FOS are increasingly used in food products and infant formulas due to their prebiotic effect that stimulates the growth of nonpathogenic intestinal microflora [18].…”
Section: Introductionmentioning
confidence: 99%